2022
DOI: 10.1038/s41467-022-28568-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of clonal selection and diversification in normal endometrial epithelium

Abstract: It has become evident that somatic mutations in cancer-associated genes accumulate in the normal endometrium, but spatiotemporal understanding of the evolution and expansion of mutant clones is limited. To elucidate the timing and mechanism of the clonal expansion of somatic mutations in cancer-associated genes in the normal endometrium, we sequence 1311 endometrial glands from 37 women. By collecting endometrial glands from different parts of the endometrium, we show that multiple glands with the same somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 92 publications
2
35
0
Order By: Relevance
“…Unlike normal colon and liver, mutant clones almost completely replace non-inflamed endometrium by menopause [29][30][31] . This is likely facilitated by the 'rhizome' structure of the endometrial epithelium, in which vertical glands acquire additional mutations during every menstrual cycle 32 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Unlike normal colon and liver, mutant clones almost completely replace non-inflamed endometrium by menopause [29][30][31] . This is likely facilitated by the 'rhizome' structure of the endometrial epithelium, in which vertical glands acquire additional mutations during every menstrual cycle 32 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A new concept that is starting to emerge is that somatic variation and the life‐long modification of each cell's genome could play a positive role in the adaptation to environmental challenges and be a critical factor shaping successful responses to tissue damage and tissue evolution. Few examples have been reported, including tissue repair during liver disease (Zhu et al, 2019 ), endometrial regeneration during menstrual cycle (Yamaguchi et al, 2022 ), and clearance of malignant clones in the esophagus (Colom et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have identified that somatic driver mutations that are thought to contribute to EC pathogenesis, including PIK3CA , KRAS and PIK3R1 , can exist in normal uteri without cancer [ 69 72 ]. We have shown that obesity regulates inflammatory pathway genes in the endometrial epithelia and disrupt the peripheral clock in the endometrial stroma.…”
Section: Discussionmentioning
confidence: 99%